2017
DOI: 10.1021/acs.chemrev.7b00027
|View full text |Cite|
|
Sign up to set email alerts
|

SERS-Activated Platforms for Immunoassay: Probes, Encoding Methods, and Applications

Abstract: Owing to their excellent multiplexing ability, high sensitivity, and large dynamic range, immunoassays using surface-enhanced Raman scattering (SERS) as the readout signal have found prosperous applications in fields such as disease diagnosis, environmental surveillance, and food safety supervision. Various ever-increasing demands have promoted SERS-based immunoassays from the classical sandwich-type ones to those integrated with fascinating automatic platforms (e.g., test strips and microfluidic chips). As re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
357
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(358 citation statements)
references
References 478 publications
0
357
0
1
Order By: Relevance
“…Surface-enhanced Raman scattering (SERS) coupled with plasmonic materials has also been used for the detection of biological species due to the high selectivity and sensitivity of the technique; thorough reviews of the use of SERS in sensing applications can be found in the literature [35,164,165]. Recently, Kim et al synthesized a label-free biosensing cellulose strip sensor with SERS-encoded bimetallic silver-gold core-shell nanoparticles (Ag@Au NPs) [76].…”
Section: Biosensorsmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) coupled with plasmonic materials has also been used for the detection of biological species due to the high selectivity and sensitivity of the technique; thorough reviews of the use of SERS in sensing applications can be found in the literature [35,164,165]. Recently, Kim et al synthesized a label-free biosensing cellulose strip sensor with SERS-encoded bimetallic silver-gold core-shell nanoparticles (Ag@Au NPs) [76].…”
Section: Biosensorsmentioning
confidence: 99%
“…6,7 In addition, such nanomaterials can be used as substrates for surface-enhanced Raman scattering (SERS) spectroscopy, with several applications in biochemistry and medicine. 8,9 A question whose answer can lead to a novel scenery is how silver nanoparticles (AgNPs) can be combined with antibiotics to face bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The fine accuracy and simple operation of immunoassays support their use in disease diagnosis, food safety, environmental protection, etc . Recently, immunoassays have evolved into sophisticated analyte‐sensing methods by employing autonomous platforms, emerging nanomaterials, and various kinds of readout signals (e.g., colorimetry, electrochemistry, surface plasmon resonance, fluorescence, and surface‐enhanced Raman scattering) …”
Section: Introductionmentioning
confidence: 99%